Mathematical problem-solving ability based on self-efficacy in junior high school. Issue 4 (June 2021) - Fatmasari, H R; Waluya, S B; Sugianto,
Abstract: Problem-solving ability is one of the standard mathematical abilities that students must have. This ability can be mastered well by students if students have affective abilities, one of which is self-efficacy. The aim of this research is to determine the ability of junior high school mathematics problem-solving based on student self-efficacy. Descriptive qualitative research is the method approach used in this research. The research subject is one student who represents the levels of self-efficacy. The results showed that students with high self-efficacy were able to master four indicators of mathematical problem-solving, students with self-efficacy were mastering three indicators, and students with low self-efficacy were only able to master one indicator. The conclusion of this research are students who have high self-efficacy are able to solve problems according to the indicators of mathematical problem-solving abilities compared to students who have medium and low self-efficacy, because students with high self-efficacy are more can to withstand math problems and do not give up hope in meeting failure. Meanwhile, students with moderate and low self-efficacy are able to solve all problems but are less able to meet the problem-solving ability indicators because they have doubts and give up easily in solving math problems.